Assessment of the humoral immune response in children after immunization with different types of inactivated influenza vaccines in the 2019-2020 season - Zh. V. Buzitskaya; A. B. Popov; E. A. Romanovskaya-Romanko; M. V. Sergeeva; E. A. Varyushina; M. K. Erofeeva; M. A. Stukova; D. A. Lioznov (Медицинская иммунология, 2023)
Causing millions of cases worldwide every year, influenza is one of the most common respiratory infections. The effectiveness of influenza vaccination and the nature of the resulting immune response may vary depending on the vaccine composition and age group. Since children are at the highest risk of disease and act as the main carriers of influenza, the assessment of the immunological efficacy of vaccines in this group is crucial for controlling the epidemic. Therefore, this study aimed to evaluate the characteristics of the humoral immune response in children after immunization with various types of inactivated influenza vaccines. An observational study was conducted in the 2019-2020 season and involved 230 children (< 18 years old) and a comparison group of 87 adults aged 18 to 60 years. The subjects, who provided informed consent to participate, were vaccinated with one of three vaccines (Grippol Plus, Sovigripp, or Ultrix) in an open-label fashion. The humoral immune response was assessed by measuring the hemagglutination inhibition (HI) titer in the paired sera taken before and three weeks after vaccination. The immunogenicity of the vaccines in the age group under 18, met the CPMP criteria for the assessment of inactivated influenza vaccines in terms of the fold increase in antibody titers and the proportion of individuals with seroconversion to all three components (A/H1N1pdm09, A/H3N2, and B/Victoria). Although 6 to 18-year-old participants showed a more robust immune response to the B/Victoria component compared to the adult participants (aged 18 to 60), it was insufficient to ensure that 70% of the participants have a protective antibody titer. A comparative analysis of the vaccines’ immunogenicity was carried out for a subgroup of children aged 6-18 who had initially low antibody levels at the time of vaccination. The analysis showed that the split vaccine Ultrix outperformed the adjuvanted vaccine Grippol Plus in generating an antibody response to the component B/Victoria; however, the antibody responses to the A/H1N1pdm09 and A/H3N2 components did not differ between the two vaccines. The children under 6 years of age demonstrated a less pronounced humoral immune response to vaccination compared with the other age groups, which may be due to the age-related characteristics of the immune system in children of preschool age.